2022
DOI: 10.1017/ice.2022.231
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for severe acute respiratory coronavirus virus 2 (SARS-CoV-2) infection among healthcare workers: A test-negative case–control study in Québec, Canada

Abstract: Objectives: In Quebec, Canada, we evaluated the risk of SARS-CoV-2 infection associated with: 1) the demographic and employment characteristics among healthcare workers (HCWs); and 2) the workplace and household exposures and the infection prevention and control (IPC) measures among patient-facing HCWs. Design: Test-negative case-control study Setting: Provincial health system Participants: HCWs with PCR-confirmed COVID-19 diagnosed between November 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…To the best of our knowledge, there are limited published data evaluating the specific impact of job roles in healthcare settings on the risk of testing positive for COVID-19, and the findings are heterogeneous. Two studies conducted in Germany reported an increased risk of testing positive for nurses and physicians compared to non-patient care occupations [ 4 , 21 ]. Additionally, a separate study indicated a higher risk among administrative personnel [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, there are limited published data evaluating the specific impact of job roles in healthcare settings on the risk of testing positive for COVID-19, and the findings are heterogeneous. Two studies conducted in Germany reported an increased risk of testing positive for nurses and physicians compared to non-patient care occupations [ 4 , 21 ]. Additionally, a separate study indicated a higher risk among administrative personnel [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Akinbami et al reported higher seroprevalence at the end of the first wave among staff in nursing homes (13%) than in hospitals (5%), 7 while our previous study in Quebec showed that working in LTCF or private seniors' homes increased the risk of SARS-CoV-2 infection compared to ACH. 10 Conversely, the relatively higher proportion of HCWs with householdacquired infections among ACH workers might be a reflection of this lower workplace risk.…”
Section: Discussionmentioning
confidence: 99%
“…The study population has been described elsewhere. 9,10 In summary, a survey was conducted among HCWs with a PCR-confirmed SARS-CoV-2 infection diagnosed between March 1, 2020, and May 31, 2021, excluding June 14 to July 11, 2020, due to the low incidence during that period. Vaccination of HCWs started on December 14, 2020.…”
Section: Study Design and Populationmentioning
confidence: 99%